2016
DOI: 10.21090/ijaerd.030445
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Exergy Analysis of Rotary Cement Kiln

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Heat and exergy analysis methods have been studied in some kilns by Parmar, et al [19], preheater and calciners by Anthony, et al [20]. Using thermodynamic analysis of processes in a raw mill was reported by Ahmet & Ahmet [21], and heat transfer analysis of exiting preheater hot gas for heat conservation goals by Sasanka & Srinivasa [22], who found that there are many opportunities left unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Heat and exergy analysis methods have been studied in some kilns by Parmar, et al [19], preheater and calciners by Anthony, et al [20]. Using thermodynamic analysis of processes in a raw mill was reported by Ahmet & Ahmet [21], and heat transfer analysis of exiting preheater hot gas for heat conservation goals by Sasanka & Srinivasa [22], who found that there are many opportunities left unexplored.…”
Section: Introductionmentioning
confidence: 99%